Red Light and Calmodulin Regulate the Expression of the psbA Binding Protein Genes in Chlamydomonas reinhardtii - Alizadeh, Darya (Oxford University Press, 2010)
In the unicellular green alga Chlamydomonas reinhardtii, translation of the chloroplast-encoded psbA mRNA is regulated by the light-dependent binding of a nuclear-encoded protein complex (RB38, RB47, RB55 and RB60) to the 5′-untranslated region of the RNA. Despite the absence of any report identifying a red light photoreceptor within this alga, we show that the expression of the rb38, rb47 and rb60 genes, as well as the nuclear-encoded psbO gene that directs the synthesis of OEE1 (oxygen evolving enhancer 1), is differentially regulated by red light. Further elucidation of the signal transduction pathway shows that calmodulin is an important messenger in the signaling cascade that leads to the expression of rb38, rb60 and psbO, and that a chloroplast signal affects rb47 at the translational level. While there may be several factors involved in the cascade of events from the perception of red light to the expression of the rb and psbO genes, our data suggest the involvement of a red light photoreceptor. Future studies will elucidate this receptor and the additional components of this red light signaling expression pathway in C. reinhardtii.